2021
DOI: 10.21037/tcr-21-1174
|View full text |Cite
|
Sign up to set email alerts
|

The clinical prognostic factors of patients with stage IB lung adenocarcinoma

Abstract: Background Lung adenocarcinoma (ADC) at stage IB has its own prognostic characteristics. This study aimed to investigate the clinical factors that may affect the prognosis of patients with stage IB ADC. Methods The data of ADC cases were selected from the Surveillance, Epidemiology, and End Results (SEER) database (2010–2016) and patients in Zhongshan Hospital, Fudan University (Department of Thoracic Surgery, 2015–2016). Kaplan-Meier method was used to obtain the overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The rapid growth of pSD compared to pGGO aligns with previous findings. Sui Q et al analyzed 7605 patients with adenocarcinoma from the SEER (Surveillance, Epidemiology, and End Results) database and concluded that female sex and age ≤ 60 years are independent prognostic factors for better survival, supporting these findings 29 . These results were also confirmed by a larger study involving 61,928 patients conducted by Wu Y et al 30 .…”
Section: Discussionmentioning
confidence: 93%
“…The rapid growth of pSD compared to pGGO aligns with previous findings. Sui Q et al analyzed 7605 patients with adenocarcinoma from the SEER (Surveillance, Epidemiology, and End Results) database and concluded that female sex and age ≤ 60 years are independent prognostic factors for better survival, supporting these findings 29 . These results were also confirmed by a larger study involving 61,928 patients conducted by Wu Y et al 30 .…”
Section: Discussionmentioning
confidence: 93%
“…Some scholars have identified risk factors influencing postoperative recurrence and have constructed predictive models for recurrence, aiming to inform the selection of ACT for stage IB NSCLC patients (91)(92)(93)(94)(95)(96). However, relatively limited research has been conducted on predictive models for postoperative recurrence in patients with stage IB NSCLC featuring VPI.…”
Section: Stage Ib and Adjuvant Chemotherapymentioning
confidence: 99%
“…Studies have reported age, race, sex, cancer location, pathologic type, airway spread through air space, and TNM staging as prognostic factors for lung cancer ( 1 5 ). Nodule features on thin-section CT images, especially nodule consistency that describes the appearance of a lung nodule, have also been proved to be important prognostic factors for lung adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%